STRATEGI TERPADU PENANGANAN PERMUKIMAN BANTARAN KANAL BANJIR TIMUR DI KOTA SEMARANG - Setyoadi, Nino Heri (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2016)
ABSTRACTEast Flood Canal handling of Semarang will not be effective without arranging illegal settlements on the riverbanks of east flood canal. Settlements arrangement on the riverbanks of east flood canal should be a priority. Settlements arrangement on the riverbanks has not been optimal. The pattern of arrangement is still sporadic, not well planed, and lack of effective coordination. This paper is designed to provide policy advice and strategies to enhance effectiveness of the settelement arrangement on the riverbanks of east flood canal. The data collection was done with secondary data documentation, indepth interviews, and observations of the condition of settlement. To analyze the data, the methods used are the technique of multi-criteria evaluation and analysis of qualitative data. In order to improve the effectiveness of the settlement arrangement, priority locations starting from the village area of Peterongan, Kedungmundu and Lamper Tengah. For the area is dominated by residential area, recommended strategy is relocating to the apartment. For the area is dominated by business activities, strategy recommended is relocating to the center of street vendors or traditional markets. For the area with a combination of residential and business activities, the recommended strategy is to integrate appartment with the center of street vendors or traditional markets in an integrated area or to ensure ease of access between appartment with the center of street vendors or traditional markets.Keywords : settlements arrangement, illegal settlement, relocation, appartment and traditional marketABSTRAKUpaya penanganan Kanal Banjir Timur kota Semarang tidak akan efektif tanpa menata permukiman di bantaran kanal banjir timur. Penataan permukiman di bantaran kanal banjir timur harus menjadi prioritas penanganan banjir kota Semarang. Penanganan permukiman bantaran kanal banjir timur selama ini belum optimal. Pola penanganan masih sporadis, belum terencana, dan belum terkoordinasi dengan efektif. Tulisan ini disusun untuk memberikan masukan kebijakan dan strategi dalam meningkatkan efektifitas penanganan permukiman bantaran kanal banjir timur. Metode pengumpulan data yang dilakukan berupa dokumentasi data sekunder, wawancara mendalam, dan pengamatan kondisi permukiman. Analisis data menggunakan teknik multi criteria evaluation dan analisis data kualitatif. Untuk meningkatkan efektifitas maka lokasi prioritas penanganan dimulai dari wilayah kelurahan Peterongan, Kedungmundu dan Lamper Tengah. Untuk wilayah dengan dominasi hunian strategi yang dilakukan berupa relokasi ke rumah susun. Pada wilayah yang di dominasi oleh kegiatan usaha, strategi yang dilakukan berupa relokasi ke sentra PKL/pasar tradisional. Wilayah dengan kombinasi antara hunian dan kegiatan usaha strategi yang dilakukan adalah mengintegrasikan rumah susun dengan sentra PKL/pasar tradisional di suatu kawasan terpadu atau dengan menjamin kemudahan akses antara rumah susun dengan sentra PKL/pasar tradisional. Kata Kunci : penanganan permukiman, permukiman ilegal, relokasi, rumah susun dan pasar tradisional